BSA Interaction, Molecular Docking, and Antibacterial Activity of Zinc(II) Complexes Containing the Sterically Demanding Biomimetic N3S2 Ligand: The Effect of Structure Flexibility - Soliman, Eman; Ibrahim, Mohamed M.; El-Khouly, Mohamed E.; El-Mehasseb, Ibrahim; Ramadan, Abd El-Motaleb M.; Mahfouz, Magdy E.; Shaban, Shaban Y.; van Eldik, Rudi (Molecules, 2022)
Two zinc(II) complexes, DBZ and DBZH(4), that have (ZnN3S2) cores and differ in the bridging mode of the ligating backbone, effectively bind to BSA. The binding affinity varies as DBZ > DBZH(4) and depends on the ligand structure. At low concentrations, both complexes exhibit dynamic quenching, whereas at higher concentrations they exhibit mixed (static and dynamic) quenching. The energy transfer mechanism from the BSA singlet excited state to DBZ and DBZH(4), is highly likely according to steady-state fluorescence and time-correlated singlet photon counting. Molecular docking was used to support the mode of interaction of the complexes with BSA and showed that DBZ had more energy for binding. Furthermore, antibacterial testing revealed that both complexes were active but to a lesser extent than chloramphenicol. In comparison to DBZH(4), DBZ has higher antibacterial activity, which is consistent with the binding constants, molecular docking, and particle size of adducts. These findings may have an impact on biomedicine.
CRIS-Team WoS Importer:2022-06-24